Prevention of mother-to-child transmission of hepatitis B virus in Burkina Faso: Screening, vaccination and evaluation of post-vaccination antibodies against hepatitis B surface antigen in newborns - Edwige T. Yelemkoure; Albert T. Yonli; Carla Montesano; Abdoul Karim Ouattara; Birama Diarra; Théodora M. Zohoncon; Christelle W.M. Nadembega; Paul Ouedraogo; Charles Sombié; Serge Theophile Soubeiga; Issoufou Tao; Adama Gansane; et al. (AOSIS, 2018)
The low rate of screening for hepatitis B virus (HBV) in pregnant women is a highrisk factor for its vertical transmission. The objectives of this study were: i) to screen pregnant women for HBV infection; ii) vaccinate all children from birth against HBV regardless their mother HBV status; and iii) evaluate after 7 months of birth the level of their AbHBs among babies who received HBV vaccine at birth. Serological markers of HBV (HBsAg, HBeAg, AbHBs, AbHBe, and AbHBc) were determined on venous blood samples from 237 pregnant women and their children using the Abon Biopharm Kit. One hundred and two (102) children received the three doses of the EUVAX B® vaccine respectively at birth, two months and four months of life. Seven months after delivery, venous blood samples were collected from mothers and their children. Antibodies against hepatitis B surface antigen (AbHBs) were measured in vaccinated children using the ELISA Kit AbHBs Quantitative EIA. DNA extraction was performed on samples from HBV-seropositive mothers and their children using the Ribo Virus (HBV Real-TM Qual) Kit and for Real Time PCR, the HBV Real-TM Qual Kit was used. Serological diagnosis in pregnant women revealed 22 (9.28%) hepatitis B surface antigen (HBsAg) positive samples of which 21 were positive for viral DNA by real-time PCR. Among the 22 HBsAg+ women, five (05) transmitted the virus to their children with a vertical transmission rate of 22.73%. A transmission rate of 23.81% (5/21) was found with the PCR method. Analysis of AbHBs levels revealed that 98.31% of the children had an average concentration of 218.07 ± 74.66 IU/L, which is well above the minimum threshold for protection (11 IU/L). This study has confirmed that vertical transmission of HBV is a reality in Burkina Faso and that vaccination at birth would significantly reduce this transmission.